Respuesta :
Answer:
See below ~
Step-by-step explanation:
P (6th grader)
- No. of 6th graders / Total students
- 6 / 6 + 7 + 8
- 6/21
- 2/7
P (6th grader after)
- No. of 6th graders - 1 / Total students - 1
- 6 - 1 / 21 - 1
- 5/20
- 1/4
Question 1 : P (Both 6th graders)
- P = P (6th grader) × P (6th grader after)
- P = 2/7 x 1/4 = 2/28 = 1/14
Question 2 : P' (Both 6th graders)
- P' = 1 - P
- P' = 1 - 1/14
- P' = 13/14
Answer:
[tex]\sf 1) \quad \dfrac{1}{14}[/tex]
[tex]\sf 2) \quad \dfrac{13}{14}[/tex]
Step-by-step explanation:
Given:
- 6 sixth graders
- 7 seventh graders
- 8 eight graders
Total = 6 + 7 + 8 = 21
[tex]\sf Probability\:of\:an\:event\:occurring = \dfrac{Number\:of\:ways\:it\:can\:occur}{Total\:number\:of\:possible\:outcomes}[/tex]
Question 1
The probability of the 1st pick being a 6th grader:
[tex]\implies \sf P(6th\:grader)=\dfrac{6}{21}=\dfrac{2}{7}[/tex]
Now there will be 5 sixth graders left and a total of 20 left.
So, the probability of the 2nd pick being a 6th grader:
[tex]\implies \sf P(6th\:grader)=\dfrac{5}{20}=\dfrac{1}{4}[/tex]
Therefore,
[tex]\implies \textsf{P(6th grader) and P(6th grader)}= \sf \dfrac{2}{7} \times \dfrac{1}{4}=\dfrac{2}{28}=\dfrac{1}{14}[/tex]
Question 2
Law of Total Probability states that the sum of probabilities is 1
[tex]\implies \textsf{P(two 6th graders) + P(not two 6th graders)}=1[/tex]
[tex]\implies \sf \dfrac{1}{14}+\textsf{P(not two 6th graders)}=1[/tex]
[tex]\implies \sf \textsf{P(not two 6th graders)}=1-\dfrac{1}{14}=\dfrac{13}{14}[/tex]